Clinical Features and Treatments Outcome of Testicular Germ Cell Tumor in Rajavithi Hospital - Chaiphonkaew, Annop; Choonhaklai, Vorapot; Akarasakul, Danaiphand; Wongwattanasatien, Nattapong; Thaidumrong, Tanet; Pumpaisanchai, Somkiat; Chittchang, Viroj (Insight Urology, 2016)
Objective: To present survival outcomes of testicular germ cell tumor after treatment in Rajavithi Hospital. Material and Methods: During June 1997 to January 2014, we retrospectively reviewed 42 patients with testicular germ cell tumor at Rajavithi hospital. Their clinical, pathology, staging, treatment and survival were analysed. Results: The mean age of the patients was 35.6 years (range:19-66 years). History cryptorchidism was found in 9 patients. Pathology results showed that, 29 patients (69%) had seminoma and 13 (31%) had non-seminoma germ cell tumors. Fourteen (33.3%) patients were stage Ia-Ib, 8(19%) patient were stage IIa-IIb and 20 (47.6%) patients were stage IIc-IIIb. After orchiectomy, 24 patients were received chemotherapy, 8 patients were received adjuvant radiotherapy, 2 patients were received RPLND, 1 patients was received neo-adjuvant plus RPLND, 6 patients were on surveillance and 1 patient was refuse for further treatment. Mean follow up was 66 months. Overall 5 years survival was 86.4% (seminoma 90.8% and non-seminoma germ cell tumors 76.9%). Conclusions: Over all 5 years survival in germ cell tumors is good. Seminoma is more common and has better outcome after treatment than non-seminoma germ cell tumors. ลักษณะทางคลินิคและผลการรักษามะเร็งอัณฑะที่เกิดจากเซลล์สืบพันธุ์ต้นกำเนิดในโรงพยาบาลราชวิถี อรรณพ ชัยพรแก้ว, วรพจน์ ชุณหคล้าย, ดนัยพันธ์ อัครสกุล, ณัฐพงศ์ วงศ์วัฒนาเสถียร, ธเนศ ไทยดำรงค์, สมเกียรติ พุ่มไพศาลชัย, วิโรจน์ จิตต์แจ้ง งานศัลยศาสตร์ยูโร กลุ่มงานศัลยศาสตร์ โรงพยาบาลราชวิถี กรุงเทพฯ บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาผลการรักษามะเร็งอัณฑะที่เกิดจากเซลล์สืบพันธุ์ต้นกำเนิด (germ cell tumor) ที่มารับการรักษาในโรงพยาบาลราชวิถี ผู้ป่วยและวิธีการศึกษา: เป็นการศึกษาแบบย้อนหลังของผู้ป่วยมะเร็งอัณฑะที่เข้ารับการรักษาที่โรงพยาบาลราชวิถี ระหว่าง มกราคม พ.ศ. 2540-มกราคม พ.ศ. 2557 จำนวน 42 คน โดยศึกษาข้อมูลทั่วไป อาการนำ ผลพยาธิวิทยา ระยะ ของโรค และผลของการรักษา ผลการศึกษา: ค่าเฉลี่ยของช่วงอายุเท่ากับ 36 ปี (ระหว่าง 19-66 ปี) ผู้ป่วย 9 รายมีประวัติมีอัณฑะข้างเดียว (cryptorchidism) ผลพยาธิวิทยาของก้อนที่อัณฑะพบเป็น pure seminoma 29 ราย (ร้อยละ 69) และ non-seminoma germ cell tumor 13 ราย (ร้อยละ 31) โดยผู้ป่วย 14 ราย (ร้อยละ 33.3) อยู่ในระยะ Ia-Ib, 8 ราย (ร้อยละ 19) อยู่ในระยะ IIa-IIb, 20 ราย (ร้อยละ 47.6) อยู่ในระยะ IIc-IIIb หลังจากการผ่าตัดเอาลูกอัณฑะออก ผู้ป่วย 24รายได้รับยาเคมีบำบัด ผู้ป่วย 8 รายได้รับการฉายรังสี ผู้ป่วย 2 รายได้รับการผ่าตัดเลาะต่อมน้ำเหลืองหลังช่องท้อง(retroperitoneal lymph nodes dissection; RPLND) ผู้ป่วย 1 รายได้รับยาเคมีบำบัดร่วมกับการผ่าตัดเลาะต่อมน้ำเหลืองหลังช่องท้อง (neo-adjuvant plus RPLND) และผู้ป่วย 6 รายได้รับการเฝ้าติดตามสังเกตอาการมีผู้ป่วย 1 รายปฏิเสธการรักษา ค่าเฉลี่ยระยะเวลาติดตามการรักษาเท่ากับ 66.6 เดือน อัตราการมีชีวิตรอดโดยรวมที่5 ปี ของมะเร็งอัณฑะที่เกิดจากเซลล์สืบพันธุ์ต้นกำเนิดเท่ากับ ร้อยละ 86.4 โดยกลุ่ม seminoma เท่ากับ ร้อยละ 90.8 และกลุ่ม non-seminoma เท่ากับ ร้อยละ 76.9 สรุป: อัตราการมีชีวิตรอดโดยรวมที่ 5 ปี ของผู้ป่วยมะเร็งอัณฑะที่เกิดจากเซลล์สืบพันธุ์ต้นกำเนิด อยู่ในเกณฑ์ดีหลังการรักษา โดยกลุ่ม seminoma มีอัตราการรอดชีวิตหลังการรักษาที่ดีกว่ากลุ่ม non-seminoma